'I know exactly who they are': Radio presenters' conceptions of audience. (1st October 2014) - Wolfenden, Helen
Since Horton and Wohl's recognition of the para-social relationship, there has been an interest in understanding the relationship between presenters and audiences beyond commodification models. But while the relationship has long been named, little is understood about the process from 'inside' the presenter experience: what audiences mean to presenters, how the relationship is constructed and becomes real in the absence of face-to-face contact when, for the most part, the presenter can only know the audience as an abstraction or a projection. This article will explore the way Australian Broadcasting Corporation (ABC) talk radio presenters construct their audience as a dialogue partner, and the way that the on-air self is managed, in line with the corporate expectations of their employer, to achieve the appropriate symbolic indicators of friendship, sympathy, companionship, disclosure and intimacy. The findings are based on interviews with leading ABC radio presenters.